Simulated Land Use/Land Cover Consistent with IMPACT Cropland Area Projections - International Food Policy Research Institute (International Food Policy Research Institute, 2022)
This dataset consists of half-degree resolution simulated land use/land cover projections (in hectares) for the entire globe for the years 2005 and 2050. The future climates are derived from five General Circulation Models (GCMs) using Representative Carbon Pathway (RCP) 8.5 (Riahi, K. et al., 2011). The Land Use and Land Cover (LULC) classes consist of nine natural vegetation categories (barren, savanna, deciduous/mixed, evergreen broadleaf forest, evergreen needleleaf forest, grassland, shrubland, tundra, and woody savanna) and twelve cropland categories (rainfed and irrigated for maize, rice, sorghum, soybeans, wheat, and all other crops). Three different data sources were used to estimate the natural vegetation component and each result simulation is reported separately. One set of cases indicates the potential area for the natural vegetation classes if there were no cropland. The second set includes cropland and thus the natural vegetation areas are reduced. The total cropland areas are derived from the IMPACT model with adjustments made for multi-cropping.